Research on rigid–flexible coupling dynamic characteristics of boom system in concrete pump truck. (23rd March 2015) - Tang, Hongbin; Ren, Wu
Concrete pump truck plays an important role in infrastructure construction and national economic development. In recent years, its boom system becomes longer, and its dynamic and control become more complicated. In order to study the dynamic characteristics of boom system, three dynamic models such as multi-rigid-body model, rigid–flexible coupling model, and rigid–flexible coupling model with equivalent hydraulic cylinder were built in this work. Simulation analysis and experimental analysis were done, and they show that we should not only consider the large-range motion but also consider the small flexible deformation to study the dynamic characteristics of boom system precisely. It provides the theoretical basis to vibration control, trajectory prediction, and life assessment for boom system and such structures.